Abandoned housing projects in Malaysia: Legal issues relating to the housing developer's licence - Md Dahlan, Nuarrual Hilal (Sweet & Maxwell Asia, 2014)
The issue of abandoned housing projects is still an unsettled issue in Malaysia.Even though there are numerous housing policies and laws having been promulgated by the government, the problem of abandoned housing projects has not yet been totally eradicated.One of the reasons leading to the occurrences of abandoned housing projects is the weaknesses of the provisions under the Housing Development Act (Control and Licensing) Act 1966 (Act 118) ("Act 118").The aim of this paper is to discuss the lacunae in Act 118.The research methodology used is a combination of legal and social research methodologies.This paper finds that there are some lacunae in the provisions of Act 118 relating to housing developers licence that need to be adequately addressed to avoid the occurrences of abandoned housing projects in Malaysia.At the ending part of this paper, the authors suggest some proposals to overcome the issues.